2016
DOI: 10.1175/wcas-d-15-0068.1
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Related Failures on Southeast England’s Railway Network: Insights and Implications for Heat Risk Management

Abstract: High temperatures and heat waves can cause numerous problems for railway infrastructure, such as track buckling, sagging of overhead lines, and the failure of electrical equipment. Without adaptation, these problems are set to increase in a future warmer climate. This study used industry fault data to examine the temporal and spatial distribution of heat-related incidents in southeast England and produce a unique evidence base of the impact of temperature on the rail network. In particular, the analysis explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 14 publications
1
35
0
2
Order By: Relevance
“…For this study, weather‐related incidents were identified from the free‐text column in FMS using an adapted algorithm developed by Ferranti et al . (). The algorithm was used to search for weather‐related keywords and phrases recorded in the database, such as: buckle, temp, expansion, hot, thermal, weather, storm, high and light.…”
Section: Datamentioning
confidence: 97%
See 2 more Smart Citations
“…For this study, weather‐related incidents were identified from the free‐text column in FMS using an adapted algorithm developed by Ferranti et al . (). The algorithm was used to search for weather‐related keywords and phrases recorded in the database, such as: buckle, temp, expansion, hot, thermal, weather, storm, high and light.…”
Section: Datamentioning
confidence: 97%
“…However, previous warm summers, such as those in 1995 and 2003, clearly show that heat severely impacts railway infrastructure (Thornes, ; Hunt et al ., ). Heat impacts upon railway assets in a variety of ways (Palin et al ., ; Ferranti et al ., ). For example, the heating of rail track in direct sunshine can lead to thermal expansion and consequential buckling of the rail.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, heavy precipitation, flooding, and strong winds of Typhoon HaiKui (August 2012) significantly disrupted rail transport, with rail, subway, and Maglev systems being suspended [7]. Although some knowledge exists on how to protect transport infrastructure from extreme weather, climate events, and climate change, and to improve network performance [8][9][10][11][12], given the sensitivity of rail transport to extreme weather, more attention is warranted. (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…While the UHI can be beneficial, that is, reduced space heating requirements (Santamouris et al, 2001), the benefits are generally overshadowed by the negative effects of excess heat during summer. These include health risks, particularly during heatwaves (Stone et al, 2010;Heaviside et al, 2016); and infrastructure, for example, railway buckling Ferranti et al, 2016). The UHI may initiate thunderstorms (Bornstein and Lin, 2000;Dou et al, 2015) and increase precipitation (Shepard et al, 2002;Dixon and Mote, 2003).…”
mentioning
confidence: 99%